Asupan Lemak dan Stres pada Masa Pandemi COVID-19 dengan Indeks Massa Tubuh Guru - Khairi, Rofifa; Mulyani, Erry Yudhya; Nadiyah, Nadiyah; Wahyuni, Yulia; Palupi, Khairizka Citra (citeus, 2021)
Based on previous research, 52% of individuals over 18 years of age experienced an increase in consumption of sweet and fatty foods during the COVID-19 pandemic as a coping with stress experienced. This study aims to analyze the relationship between fat intake and stress during the COVID-19 pandemic with the body mass index of teachers. This cross sectional research was conducted at SMKN 1 Jambi City, using a simple random sampling method. Subjects were teachers with civil servant and honorary status as many as 56 people. Subject characteristics, anthropometric data, fat intake and stress were taken using a questionnaire. Food recall 3x24 hours is used to view fat intake data. Perceived stress scale (PSS) is used to view stress data. The majority of the subjects were 41.2 ± 3.7 years old; body weight 58.2 ± 7.2 kg; height 158 ± 6.4 cm; BMI 23.2 ± 2.6 kg / m2; fat intake of 61.6 ± 11.9 grams and a PSS score of 20.5 ± 3.8. There is a relationship between fat intake and body mass index during the COVID-19 pandemic because (p˂ 0.05) and there is no relationship between stress and body mass index during the COVID-19 pandemic because (p≥0.05). Further research regarding fiber intake and body fat percent is recommended